Developing behavioural indicators for intellectual functioning and adaptive behaviour for ICD‐11 disorders of intellectual development. Issue 5 (9th January 2019) - Tassé, M. J.; Balboni, G.; Navas, P.; Luckasson, R.; Nygren, M. A.; Belacchi, C.; Bonichini, S.; Reed, G. M.; Kogan, C. S.
Abstract: Background: We present the work conducted to arrive at deriving behavioural indicators that could be used to guide clinical judgement in determining the presence and severity of deficits in intellectual functioning and adaptive behaviour for the purpose of making a diagnosis of disorders of intellectual development. Methods: An interdisciplinary expert panel provided guidance in developing behavioural indicators for intellectual functioning. A national dataset of adaptive behaviour on a sample of individuals with a diagnosis of intellectual disability was used to develop the behavioural indicators for the adaptive behaviour. The adaptive behaviour data were analysed using a cluster analysis procedure to define the different severity groupings by chronological age groups. Results: We present a series of tables containing behavioural indicators across the lifespan for intellectual functioning and adaptive behaviour, including conceptual, social and practical skills. These tables of behavioural indicators have been proposed for use in the clinical version of the 11th revision of the International Classification of Diseases and Related Health Problems (ICD‐11) to be published by the World Health Organization. Conclusions: The proposed behavioural indicators for disorders of ID described in the present article and to be included in the ICD‐11 Clinical Descriptions and Diagnostic Guidelines are put forth to assist professionals in making an informed clinical decision regarding an individual's level of intellectual functioning and adaptive behaviour for the purpose of making a determination about the presence and severity of disorders of ID.